TRENDS IN ENTREPRENEURSHIP TRAINING OF MASTERS IN THE FIELD OF EDUCATION IN THE REPUBLIC OF FINLAND - Olena Tadeush (Неперервна професійна освіта: теорія та практика)
The article identifies and summarizes trends in entrepreneurial education of masters in the field of education in the Republic of Finland in the period 2010-2025 at pan-European, national and institutional levels. It is noted that the Republic of Finland is a leader in the implementation of entrepreneurship training initiatives in higher education institutions in the European Union, which determined the choice of this country for the study of trends in entrepreneurship training for masters of pedagogical specialties. The author analyzed and classified the trends of entrepreneurship education of masters of pedagogical specialties in the Republic of Finland, according to the defined criteria: strategic-target, organizational-content, result-prognostic. The main areas of strategic purpose in the Republic of Finland are defined as: launch of national entrepreneurship education strategies; development and implementation of state educational programs for entrepreneurship training; the strategic priority of entrepreneurship training at all levels of education; financing of entrepreneurship development projects at pan-European, national, regional, and local levels; partnership of the state, educational institutions and business institutions in the organization of entrepreneurship training at all levels of education. The trends of organizational and substantive purpose include: changing the concept of entrepreneurship education in the processes of professional training of specialists of various profiles in higher educational institutions; organizational measures aimed at increasing motivation to study entrepreneurship among students of higher education as one of the career options; modernization of educational programs for the professional training of specialists in the field of education in higher education institutions in order to include sustainable and social entrepreneurship in educational programs based on an interdisciplinary approach and the use of modern digital resources; involvement of leading experts in the entrepreneurial field in the teaching process (practitioners, entrepreneurs, graduates); expansion of strategic areas of entrepreneurial education by increasing partnership cooperation of universities at the level of the European Union. The main trends of the result-prognostic are determined: the spread of experience in teaching entrepreneurship of masters of pedagogical specialties; increasing the attractiveness of teaching entrepreneurial activities of teachers as one of the career options; expansion of strategic areas of entrepreneurial education by strengthening partnership cooperation of universities at the level of the European Union. The main trends of a productive and prognostic nature have been determined: the spread of the experience of teaching entrepreneurship of masters of pedagogical specialties; increasing the attractiveness of entrepreneurial activity of teachers as one of the career options. It noted that the experience of entrepreneurship education of masters of pedagogical specialties in the universities of the Republic of Finland can serve as a reference point for the modernization of educational programs of professional training of masters of pedagogical specialties in universities of Ukraine.